2017
DOI: 10.1186/s40068-017-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Household level tree planting and its implication for environmental conservation in the Beressa Watershed of Ethiopia

Abstract: Background: Elsewhere in other developing countries, and 85% of the Ethiopian population is living in rural part of the country and more than 90% of domestic energy source is dependent of traditional biofuel. Increase in population is causing more demand for human use and more pressure on natural resources. This adversely affect the increase of multi-purpose and indigenous tree plantation and ago-forestry practice and hence has a vicious circle with food security. However, following the start of community base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
(20 reference statements)
0
13
0
1
Order By: Relevance
“…This represents a clear sign of energy insecurity when a household burns a fuel that they prefer to use for another purpose and could potentially be a robust indicator to enhance measurement of household energy insecurity to complement fuel/energy poverty measures. Recent case study research from the highlands of Ethiopia using mixed methods confirmed the continued existence of this chronic household energy insecurity as a negative feedback of biomass removal from the environment leading to less biomass being regenerated and available to the community [56]. Firewood remained overall the most frequently used energy source for the ERHS households but was often collected in open access areas or in communal forests, as well as from on-farm sources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This represents a clear sign of energy insecurity when a household burns a fuel that they prefer to use for another purpose and could potentially be a robust indicator to enhance measurement of household energy insecurity to complement fuel/energy poverty measures. Recent case study research from the highlands of Ethiopia using mixed methods confirmed the continued existence of this chronic household energy insecurity as a negative feedback of biomass removal from the environment leading to less biomass being regenerated and available to the community [56]. Firewood remained overall the most frequently used energy source for the ERHS households but was often collected in open access areas or in communal forests, as well as from on-farm sources.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the promotion of common environmental assets and on-farm tress may be complimentary, rather than substitutive, goals. Recent research from a watershed management area in Ethiopia confirmed that household level trees were major contributors to achieving project goals by meeting community fuel and fodder needs while relieving pressure on existing forests and at the same time increasing productivity by increasing dung availably for fertilizer [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the area during the last 35 years, based on the author's observations, the distribution and pattern of rainfall could be classified as uneven, irregular and erratic. Therefore, has considerable contribution to low crop production, food shortage and insecurity (Worku et al 2017b). Therefore, depending on the historical trend of rainfall variability and prolonged increase of surface temperature, optimization of supplemental irrigation from harvested water would be useful during excess rainfall and runoff when rainfall is over.…”
Section: Optimization Of Supplemental Irrigationmentioning
confidence: 99%